Analysis of the nutritional quality of maize silage in the years 2011-2019 and the relationship between the microclimatic conditions and nutritive value of silage from Slovakia - Matúš Rajský; Zuzana Mlyneková; Zuzana Formelová; Ondrej Hanušovský; Miroslav Juráček (Journal of Central European Agriculture)
The aim of the experiment was to analyze the nutritive value of maize silage through the 9-year monitored period in relationship to precipitation and temperature during the growing season in Slovakia. In the maize silage samples (1204) the basic nutrients were analyzed according to 3 regions and 8 counties according to the statistical analysis methods. The statistical evaluation of results was realized by IBM SPSS ver. 26.0. The descriptive statistics of nutritive value of maize silage by One-Way ANOVA, the significant differences by POST HOC Tukey test (P < 0.05), and for the relationship between the nutrients and microclimatic conditions Pearson correlation test (r) was realized. The results confirmed that the nutritive value of maize silage is significantly affected by year, region, and county. The strongest effect of precipitation on the dry matter (DM), ether extract (EE), nitrogen-free extracts (NFE), crude fiber (CF), acid detergent fiber (ADF) and neutral detergent fiber (NDF) was observed. In contrast, the effect of temperature on the content of dry matter and etheric extract was reflected. The positive significant effect of precipitation during April and July on the starch content was determined. Then, temperatures in June significantly increased the DM and NFE content. On the other hand, temperatures caused a significant decrease in EE, CF, ADF, and NDF in maize silage in June.